Tópicos de aritmética: uma proposta para a educação básica - Alcântara, Francisco Ailton (2014)
This paper presents arithmetic topics related to the study of the division, for use in the high school classroom, whose purpose is to seek further knowledge of arithmetic that the students learn in elementary school. We begin with the approach of the main properties of divisors, the division algorithm and the motto of the remains. Then we study the prime numbers with special attention to the fundamental theorem of arithmetic, of paramount importance in achieving many important results in this text. Further down, the definitions of greatest common divisor and least common multiple and the characterizations, properties and geometric interpretation. As a proposal for continuing the studies of division in high school, we present an elementary study about the congruence module m and its application in demonstrating of the criteria for divisibility. Finally, we expose an implementation report of the topics of this paper in the classroom.